2019
DOI: 10.3390/molecules24183372
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Modulation as a Treatment of Amyloid Diseases

Abstract: Amyloids are fibrous proteins aggregated into toxic forms that are implicated in several chronic disorders. More than 30 diseases show deposition of fibrous amyloid proteins associated with cell loss and degeneration in the affected tissues. Evidence demonstrates that amyloid diseases result from protein aggregation or impaired amyloid clearance, but the connection between amyloid accumulation and tissue degeneration is not clear. Common examples of amyloid diseases are Alzheimer’s disease (AD), Parkinson’s di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 129 publications
(192 reference statements)
1
40
0
Order By: Relevance
“…Our findings showing increased gene expression of PRKAG2, a positive regulator of autophagy suggest that it may be a contributing factor to autophagy induction in AD. The autophagy pathway is impaired at different steps in neurodegenerative diseases and mostly associated with increased autophagy initiation and reduced autophagosome degradation [1,15]. Our findings showing increased PRKAG2 gene expression in AD combined with a positive association with A␤ levels suggest that PRKAG2 dysfunction is specific to AD and related to A␤ accumulation, a pathological hallmark of AD.…”
Section: Discussionmentioning
confidence: 69%
“…Our findings showing increased gene expression of PRKAG2, a positive regulator of autophagy suggest that it may be a contributing factor to autophagy induction in AD. The autophagy pathway is impaired at different steps in neurodegenerative diseases and mostly associated with increased autophagy initiation and reduced autophagosome degradation [1,15]. Our findings showing increased PRKAG2 gene expression in AD combined with a positive association with A␤ levels suggest that PRKAG2 dysfunction is specific to AD and related to A␤ accumulation, a pathological hallmark of AD.…”
Section: Discussionmentioning
confidence: 69%
“…is impairment in autophagic flux may be secondary to either impairment in axonal trafficking or insufficient lysosome acidification [67,68]. Recent studies show that AMPK activation not only enhances autophagosome formation but also enhances autophagosome clearance.…”
Section: Ampk and Aβ Metabolismmentioning
confidence: 99%
“…AD is characterized by the accumulation of unwanted toxic protein aggregates including tau neurofibrillary tangles and Aβ aggregates (oligomers, fibrils, and senile plaques) [2]. From previous studies, it has been found that the protein quality control and the cellular defense system has failed severely during AD progression [348]. The impact of AD pathogenesis can be found at all the levels of the proteostasis network.…”
Section: Proteostasis Failure In Admentioning
confidence: 99%